Analisis Pengaruh Inflasi Dan Suku Bunga Terhadap Pertumbuhan Ekonomi di Kota Kupang Tahun 2013-2022 - Daniel Naramesakh; Maria Indriyani Hewe Tiwu; Fransina W. Ballo (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
The purpose of this study is to determine the magnitude of the influence of inflation and interest rates on economic growth in Kupang City. The research used is quantitative research analyzed using the help of the SPSS (statistical package for the social sciences) time series data software program. The data collection for this study is secondary data from the East Nusa Tenggara Central Statistics Agency and Bank Indonesia in 2013-2022 in the form of quarters (time series) in NTT Province. The results of the study show that the results of the regression analysis, inflation does not have a significant effect on economic growth in Kupang City during the 2013-2022 period. The results of the partial test (t-test) show that changes in interest rates play a role in determining the dynamics of economic growth, where lower interest rates tend to encourage increased investment and consumption, while higher interest rates have the potential to restrain economic activity because they increase borrowing costs. The results of the simultaneous test (F test), inflation and interest rates have a significance value of less than 0.05, which means that both variables simultaneously play a role in determining economic growth. The coefficient of determination (R²) value of 35.11% indicates that only a small portion of the variation in economic growth can be explained by inflation and interest rates. The remaining 64.89% is influenced by other factors outside the model, such as investment levels, government spending, unemployment rates, fiscal policies, and external factors such as global commodity prices and national economic conditions.